Pemberdayaan Masyarakat Melalui Program Budidaya Tanaman Organik Di Gampong Lambhuk Kecamatan Ulee Kareng Kota Banda Aceh - Depi, Putri Depiana (Program Studi Kesejahteraan Sosial Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Islam Negeri Ar-Raniry, 2024)
Community empowerment can be done through the agricultural and plantation sectors. In Aceh, especially in Gampong Lambhuk, one of the implementations of community empowerment is through an organic plant cultivation program. This research aims to determine the model of community empowerment through an organic plant cultivation program and its impact on improving social welfare in Gampong Lambhuk, Ulee Kareng District, Banda Aceh City. This research method uses a qualitative approach with descriptive research type. Data collection techniques are carried out through interviews, observation and documentation. The research results show that the community empowerment model through an organic plant cultivation program in Gampong Lambhuk, Ulee Kareng District, Banda Aceh City is a participatory model that involves the local community and does not involve outside parties, both in terms of program planning, implementation and the evaluation stages of the activities carried out. The impact of the organic plant cultivation program on improving social welfare in Gampong Lambhuk, Ulee Kareng District, Banda Aceh City is in the form of community health aspects with the availability of healthy and nutritious food, which can help the community to maintain their health. Another impact can be reducing air and air pollution due to the use of pesticides and synthetic fertilizers.